Internet For Seniors in Easy Steps : For the Over 50s - Price, Michael, 1942- and Price, Sue (Southam, Warwickshire, England Computer Step, 2006)
Provides information for the older readers on the features and functions of using the internet
Include Color Illustration and Index
Keywords: Internet and older people -- Internet -- Computers and older people